Implementasi Program Team Building Berbasis Cooperative dalam Upaya Mengatasi Stres dan Meningkatkan Kognisi Sosial pada Siswa Kelas XI di SMA Negeri 5 Palembang - Sapri Yani; Rina Oktaviana (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2026)
This community service program aimed to describe the implementation of a team-building program based on cooperative games as an effort to reduce academic stress and enhance social cognition among eleventh-grade students at SMA Negeri 5 Palembang. The methods employed in this community service activity included observation and interviews, supported by instructional media designed to strengthen students’ learning experiences during cooperative game activities. The results indicated that the cooperative games–based team-building program was implemented effectively, in a well-structured manner, and in accordance with its objectives. Activities emphasizing cooperation, active participation, and experiential learning created a more relaxed, enjoyable, and supportive learning environment, thereby helping to reduce students’ academic stress. Students demonstrated increased enthusiasm, focus, and openness in social interactions. Furthermore, the program had a positive impact on students’ social cognition by improving interpersonal communication, empathy, mutual trust, and shared responsibility, while also fostering more inclusive social relationships among students.